Individual Differences in Investor Decision-making: Examining Representativeness Heuristics and Cognitive Reflection - Ruhollah Amareh; Esfandyar Malekian; Hossein Fakhari (Iranian Journal of Accounting, Auditing & Finance)
Due to limited cognitive resources, investors often utilize mental shortcuts to make quick judgments. This study examines the impact of representativeness heuristics (Conjunction Fallacy, Gambler's Fallacy, and Stereotypes) and the Cognitive Reflection Test (CRT) on investor decision-making. The population of this study consists of a sample of investors in the Tehran Stock Exchange. The study employs a Chi-Square test (χ^2) to explore the relationship between heuristics and CRT, along with T-tests, one-way ANOVA, and correlation analyses to identify individual differences. Results indicate that proper utilization of cognitive resources can partially prevent the Conjunction Fallacy from occurring. Moreover, investors tend to consider the high probability of consecutive results for an event regardless of cognitive resource usage. Interestingly, this study also found that investors with lower CRT scores made decisions less influenced by stereotypes. We conclude that reducing the impact of representativeness heuristics can be achieved through knowledge and experience gained from similar situations and appropriately utilizing cognitive resources.